(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to present the obstetric and perinatal outcomes of twin pregnancies that were followed up by our clinic, for three years.Material and Methods: The twin pregnancies, which were followed up during their whole gestational periods and delivered in our clinic, from the year 2016 to 2019, were observed retrospectively for their obstetric and perinatal outcomes.Results: 56 twin pregnancies were enrolled in the study, 48 (85.7%) of which were conceived spontaneously, and 8 of which were conceived with assisted reproductive techniques. 48 (85.7%) of all twins were dichorionic (DC) diamniotic, 7 of them (12.5%) were monochorionic (MC) diamniotic, and 1 of them ( 1.78%) was MC monoamniotic. Ages of mothers, a gestational week at delivery, way of delivery, birth weights of newborns, and complications like preterm labor, the discordance of twin pairs, intrauterine fetal demise, twin to twin syndrome (TTTS), and twin anemia- polycythemia sequence were examined. Preterm labor was observed in 22 (39.3%) twin pregnancies, and the discordance rate was 21.4%. In 5 of them (8.9%), TTTS developed. One of the twin pair died in 5 (8.9%) of all. 1 (1.8%) conjoined twin was observed and delivered at term. Forty-eight of all twin pregnancies (85.7%) delivered by caesarian section, 6 of them (10.71%) by the vaginal route, and 2 of them (3.51%) ended with a miscarriage.Conclusions: Twin pregnancies are high-risk pregnancies when the fetal and maternal outcomes are in concern. Chorionicity is the most important factor effective in perinatal outcomes. Early recognition of the complications, mainly belonging to MC twins, and frequent antenatal follow up will help to intervene at the correct time and decrease fetal and maternal complication rates.Keywords: Twin pregnancies; chorionicity; obstetric; perinatal outcome